Calculations for parameters of a stationary reflex discharge - Kovtun, Yu.V.; Ozerov, A.N.; Skibenko, A.I.; Skibenko, E.I.; Yuferov, V.B. (Вопросы атомной науки и техники, 2015)
A variant of the stationary reflex discharge model based on the global (volume-averaged) model is under consideration. The calculation is carried out on the plasma electron density and temperature as a function of the adsorbed power in the reflex discharge, magnetic field value and initial gas pressure. The density of neutral atoms and cathode material ions coming into the discharge by the cathode sputtering mechanism is determined.